Implementation MPPT Using CUK Converter with Enchanced Haris Hawk Optimization Algorithm in Partial Shading Conditions - Muhammad Nizar Habibi; Faiz Rivaldi Fi'Adha; Rahmad Habibulloh; Dhea Ayu Nirmala Sari; Hasnira; Novie Ayub Windarko (JURNAL INTEGRASI, 2026)
Photovoltaic system efficiency drops significantly under Partial Shading Conditions (PSC) due to multi-modal power characteristics. Conventional algorithms and standard metaheuristics like Harris Hawks Optimization (HHO) frequently suffer from premature convergence and local peak entrapment. To resolve this, an Enhanced Harris Hawks Optimization (EHHO) strategy integrated with a continuous-current CUK converter is proposed for Maximum Power Point Tracking (MPPT). EHHO revitalizes the search mechanism using logarithmic, exponential functions, and a traveling distance rate to definitively prevent local optima entrapment. Simulations verify that EHHO delivers a superior average tracking accuracy of 99.43% within 0.260 s. In direct contrast, benchmark algorithms (PSO and HHO) exhibit severe performance degradation due to deceptive local peaks. Furthermore, EHHO yields the highest cumulative energy harvest of 27.44 Ws, confirming its absolute robustness in maximizing energy extraction within dynamic environments.